EPISTIMOLOGI USHUL FIQH DALAM KONSTRUK HISTORIS - Sakirman, Sakirman (IAIN Kediri, 2016)
At the time of the Prophet was alive all the issues were based on the revelations and ordinances of the prophet. However, when the prophet had died of Muslims find it difficult to decide on various issues, especially relating to new problems that have not been mentioned in the Qur'an and Sunnah. Therefore, after the death of the prophet every cleric diligence to provide answers to the problems faced by law. In the historical development of usul fiqh was recognized two categorization are dominate the thinking of ushul fiqh, ushul mutakalimin and ushul hanafiyah. Ushul mutakalimin was recognized as ushul is rasionalis, ushul Hanafiyah was recognized as ushul was doctriner. But, majority of moslem scholar express that nearest by al-ra'yi was sect Hanafi was desain from the beginning theory al- Syafi’i is cope to look for the road; street sintesis from second of the tendency.